Highly efficient and enantioselective synthesis of β-heteroaryl amino alcohols via Ru-catalyzed asymmetric hydrogenation. Issue 91 (28th October 2022) - Wu, Chao; Ma, Baode; Chen, Gen-Qiang; Zhang, Xumu
Abstract : We herein report a highly enantioselective hydrogenation of α- N -heteroaryl ketones catalyzed by chiral ruthenium catalysts, furnishing β-heteroaryl amino alcohols in superb yields and enantioselectivities (up to 99% yield and up to 99% ee). Abstract : Chiral β-heteroaryl amino alcohols are key fragments of many bioactive compounds and antibiotics, and the development of efficient synthetic methods for these compounds is of great value. The highly enantioselective hydrogenation of α- N -heteroaryl ketones was realized with a ruthenium-diphosphine–diamine catalyst, providing the corresponding chiral β-heteroaryl amino alcohols with up to 99% yield and up to >99% ee. The synthetic utilities of the current reaction were demonstrated by gram-scale synthesis of key intermediates of Sertaconazole and Cenobamate.